A history of underwear : with Professor Chicken - Holt, Hannah (Roaring Brook Press, 2022)
From Paleolithic loincloths to Henry VIII's wives wearing underwear on their heads and beyond, this hilarious--and accurate--history of underwear (as comically modeled by chickens), tells the fascinating story of our most private clothing.